An Overview of Comet Assay Application for Detecting DNA Damage in Aquatic Animals - Jiang, Nan; Naz, Saima; Ma, Yulin; Ullah, Qudrat; Khan, Muhammad Zahoor; Wang, Jiaqi; Lu, Xuan; Luosang, Dun-Zhu; Tabassum, Sadia; Chatha, Ahmad Manan Mustafa; Basang, Wang-Dui (Agriculture (Basel), 2023)
This review discusses several research studies that employed comet assay to evaluate the environmental impact of genotoxins in aquatic environments. It focuses on in vivo and in situ studies of aquatic animals. New chemicals are being added each year to the existing burden of toxic substances in the environment. Excessive agricultural and industrial activities adversely affect biodiversity, threatening the survival of species in a particular habitat, as well as posing disease risks to humans. Some of the chemicals, e.g., pesticides and heavy metals, may be genotoxic to the sentinel species and/or to non-target species, causing deleterious effects in somatic or germ cells. Comet assay is a quick, sensitive, and low-cost technique for detecting DNA strand breakage. However, the comet assay has much more to offer than being an assay for testing DNA strand breaks in animal organs. The use of repair enzymes increases the range of DNA lesions that can be detected with the assay. Comparing data from studies that employed different approaches, such as empirical scoring or comet tail lengths, comet assay is one of the challenging techniques to be utilized in environmental studies. The relative amount of DNA in the comet tail indicates DNA break intensity. The assay has been modified to detect various base alterations by including the digestion of nucleoids with a lesion-specific endonuclease. The determination of DNA damage in these indicator species using the comet test would thus offer information on the genotoxic potential of their habitat at an early stage. This would enable intervention techniques to prevent or mitigate adverse health impacts in sentinel animals and humans.